Modeling of swordtip squid (Uroteuthis edulis) monthly habitat preference using remote sensing environmental data and climate indices - Haghi Vayghan, Ali; Ray, Aratrika; Mondal, Sandipan; Lee, Ming-An (Frontiers in Marine Science, 2024)
Forage fish play a pivotal role in marine ecosystems and are highly valuable worldwide. Fast-growing, short-lived, and essential to the maintenance of trophic webs, squid provide an adaptable surrogate for tracking the impact of environmental change on species-appropriate habitats. This study applied oceanography data and climate indices as well as catch data in Taiwan waters to model the monthly habitat preference of swordtip squid. Among seven oceanographic characteristics, bottom sea temperature (SSTB), sea surface height (SSH), sea surface chlorophyll (SSC), and sea surface temperature (SST) had the highest influence in generalized additive model (GAM) analysis (deviance explained: 40.30%); thus, these were deemed the main variables affecting swordtip squid distribution. Monthly six climatic oscillations were also considered for the calculation of the monthly catch rate of swordtip squid; Pacific Decadal Oscillation (PDO: 31%) had more influence on its distribution, followed by North Pacific Gyre Oscillation (NPGO: 10.8%) and Western Pacific Oscillation (WPO: 6.05%). The SSTB, current pattern, and food index were the main factors affecting the monthly distribution of swordtip squid. Between 2015 and 2019, the primary squid fishing grounds were located in the northeastern waters of Taiwan, specifically within the geographical coordinates of 25°N to 28°N and 121.5°E to 125°E. Given the commercial value of swordtip squid, habitat trend modeling with an emphasis on hotspot regions should be conducted to establish possible management strategies for ensuring future sustainable fisheries. In a broader context, research involving climatic oscillations and habitat modeling can be viewed as essential to the management of sustainable fisheries because it can offer important insights into the intricate relationships that exist between the climate, oceanography and Indian Ocean swordfish as well as other fisheries. This knowledge can help decision-makers make decisions that will protect the productivity and long-term health of fisheries.